Fish protein hydrolysate in diets for Nile tilapia post-larva - Silva, Thiberio Carvalho da; Rocha, Joana D'Arc Mauricio; Moreira, Pedro; Signor, Altevir; Boscolo, Wilson Rogerio (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to determine the apparent digestibility coefficient (ADC) of crude protein, crude energy, fat, and dry matter of fish protein hydrolysate (FPH), made of by-products of Nile tilapia (Oreochromis niloticus) and whole sardines (Cetengraulis edentulus), and to evaluate the productive performance and muscle fiber growth of Nile tilapia post-larvae. Two trials were conducted, the first one to determine the digestibility in 120 fingerlings (70.0±2.0 g), and the second one to evaluate the productive performance of 375 post-larvae, with three days of age, which were distributed in 25 aquaria with 30 L of useful volume. Five diets were prepared based on vegetable ingredients, to which fish were included at 0, 2, 4, 6, and 8% FPH. For the evaluation of muscle growth, eight fish of each experimental unit were used. The ADC values found were: 98.29% for dry matter; 99.28% for crude protein; and 99.13% for gross energy. The best zootechnical response for the productive performance resulted from the treatment with the inclusion of fish hydrolysate at 4.75%. The diets affected the frequency of the muscle fiber diameters, mainly the growth by hyperplasia. FPH can be efficiently used, and its inclusion at 4.75% is indicated in the diets for Nile tilapia in the post-larvae stage.